ATM Card Cloning and Ethical Considerations. - Kaur, Paramjit; Krishan, Kewal; Sharma, Suresh K.; Kanchan, Tanuj (Science & Engineering Ethics, 2019)
With the advent of modern technology, the way society handles and performs monetary transactions has changed tremendously. The world is moving swiftly towards the digital arena. The use of Automated Teller Machine (ATM) cards (credit and debit) has led to a "cash-less society" and has fostered digital payments and purchases. In addition to this, the trust and reliance of the society upon these small pieces of plastic, having numbers engraved upon them, has increased immensely over the last two decades. In the past few years, the number of ATM fraud cases has increased exponentially. With the money of the people shifting towards the digital platform, ATM skimming has become a problem that has eventually led to a global outcry. The present review discusses the serious repercussions of ATM card cloning and the associated privacy, ethical and legal concerns. The preventive measures which need to be taken and adopted by the government authorities to mitigate the problem have also been discussed.